Effect of non surgical periodontal therapy and vitamin C supplementation on total antioxidant capacity in patients with chronic generalised periodontitis - A randomised controlled trial - Swet Nisha; Avinash Bettahalli Shivamallu; Akila Prashant; Pratibha Shashikumar; Aruna Ganganna; Debanjan Das (Elsevier, 2023)
Background: Periodontal inflammation are inflammation of supporting tissues of periodontium. The microbial factor can cause infection which is polymicrobial in origin and causes dysbiosis and shift in oxidative stress with compromised antioxidant capacity. This study focused at determination of the effect of nonsurgical periodontal therapy (NSPT) and vitamin C supplementation on total antioxidant capacity (TAOC) in chronic periodontitis patients (ChP). Material & method: A total of 70 ChPand 35 periodontally healthy subjects (control) were recruited in this study. Further, ChP group was subdivided into ChP1 group (n = 35) which received NSPT only and ChP 2 group (n = 35) which received NSPT with vitamin C 500 mg once daily for 3 months. Serum and saliva samples were taken at baseline and at 3 months postNSPT for measurement of TAOC. Clinical parameters measured were measured at 1-, 3-, 6- and 12-month interval. Results: Lower levels of serum and salivary TAOC levels were observed in ChP patients than healthy subjects (p < 0.05). Improvement in Clinical parameters was observed in both the groups ChP1 and ChP 2 group post therapy (p < 0.05). The periodontal treatment showed insignificant changes in serum and salivary TAOC levels (p > 0.05). The supplemental dose of vitamin C didn't have any additional benefits (p > 0.05). Conclusion: There lies an association of oxidative stress with periodontitis, low serum and salivary TAOC levels were seen in chronic periodontitis patients. NSPT improved the periodontal inflammatory status. However, benefits of vitamin C as an adjunct to NSPT remains inconclusive and needs to be further explored by multicentre longitudinal studies.